1996
DOI: 10.1121/1.415856
|View full text |Cite
|
Sign up to set email alerts
|

Sound transmission to and within the human ear canal

Abstract: Sound transmission to the eardrum from various points in the external ear was measured by means of probe microphone technique. Twelve human subjects participated, and three directions of sound incidence were included. For the major part of the audio frequency range the transmission to the eardrum proved independent of direction from points at the centerline of the ear canal, including the entrance (open or blocked). The results further suggested that the region with independent transmission extends some millim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 12 publications
5
66
1
1
Order By: Relevance
“…The ear canal can be modeled as a transmission line (acoustical waveguide) as presented, e.g., in [6] and later discussed, e.g., in [2].…”
Section: Ear Canal Modeling and Estimation Of Pressure At Eardrummentioning
confidence: 99%
“…The ear canal can be modeled as a transmission line (acoustical waveguide) as presented, e.g., in [6] and later discussed, e.g., in [2].…”
Section: Ear Canal Modeling and Estimation Of Pressure At Eardrummentioning
confidence: 99%
“…With proper equalization these measurements can re-create the sound spectrum at the tympanum (Kulkarni and Colburn 1998). The HRTFs measured at the tympanum can be separated into 2 terms: one that varies with direction of incidence, and another term that contains the nondirectional transfer function of the ear canal (e.g., Hammershøi and Møller 1996). The directional part of the HRTF can be measured at a distance of a few millimeters from the entrance of the blocked ear canal.…”
Section: Generation Of the Virtual Auditory Environmentmentioning
confidence: 99%
“…As the radiation impedance (Z r ) does not include the part of the sound incidence direction in Eq. (13), we found that the transmission characteristics of the ear canal are not affected by the sound incidence direction [5].…”
Section: Resultsmentioning
confidence: 63%